Central Asia in the Conditions of Conjugation of the Economic Belt of the Silk Way and the Eurasian Economic Union - Vatanyar Saidovich Yagya (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article analyzes soft power in the policices of China and Russia in Central Asia from the perspective of successful realization of interaction of the Economic Belt of the Silk Way and the Eurasian Economic Union. It especially emphasizes that in combination with the Eurasian Economic Union, the Economic Belt of the Silk Way presents new characters in configurations of international economic and political relations.